Upaya Pengendalian Penyakit Hipertensi dan Diabetes Mellitus pada Masyarakat Pulau Nguan - Didi Yunaspi; Desi Ernita Amru; Huzaima Huzaima; Catur Yulinawati; Desi Pramita Sari; Renny Adelia Tarigan (PPNI UNIMMAN, 2024)
Hypertension and diabetes mellitus are significant health issues that can lead to serious complications such as cardiovascular diseases, stroke, and kidney failure. Efforts to control these diseases are essential to improving the quality of life for communities. Based on this background, the community service team from Mitra Bunda Health Institute organized health education and screenings on Nguan Island, Batam City. This initiative aimed to provide prevention and management of hypertension and diabetes mellitus for residents of RT 001 and RT 002 of Nguan Island. The implementation methods included blood pressure and blood sugar tests, health education through visual media, and health promotion adhering to health protocols. The high level of community participation reflects a positive response to efforts aimed at preventing and managing these diseases. Evaluation results show that the activities were successfully carried out, with participants following health education sessions and screenings in an orderly manner according to the established health protocols. Collaboration among the community, cadres, neighborhood heads, and local authorities has had a positive impact on raising awareness about the importance of managing hypertension and diabetes mellitus. These activities are planned to be conducted regularly to create a healthier environment on Nguan Island. Full support from various parties is essential to ensure the sustainability of this program for the improvement of community health.